FTIR SPECTROSCOPY AND DIELECTRIC PROPERTIES OF RECONSTITUTED BUFFALO POWDERED MILK WITH WATER - 1K.Rajitha, 2N.Manohar Reddy (Chelonian Research Foundation, 2023)
Fourier transform infrared (FTIR) spectroscopy in the mid-infrared (400 - 4,500 cm-1) was carried out to investigate the conformation of chemical composition (proteins) in the present reconstituted buffalo powdered milk. Dielectric properties of milk play an important role when milk powder is reconstituted with water. Data on the analysis of dielectric properties, such as the dielectric constant, are reported in the paper, dielectric loss and electrical conductivity of reconstituted buffalo powdered milk with water at different concentrations of milk ranging from 0.5 to 5 gm/100ml were carried out at audible frequencies ranging from 100 Hz to 25k Hz, using digital LCZ meter. Keywords: FTIR, Buffalo milk powder, Reconstitution, Dielectric constant, Dielectric loss, electrical conductivity, Impedance analyzer.